Debunking the yule log myth the disturbing history of a plantation legend - May, Robert E. 1943- (Rowman & Littlefield, 2025)
"In this book historian Robert May takes readers on a detective caper as he corrects the historical record centered around enslaved people and a mythical freedom that the burning of a yule log was believed to have brought them during the holiday season."
Keywords: Geschichte 1860; Idealisierung; Brauch; Weihnachten; Sklave; USA -- Südstaaten; Enslaved persons / Southern States / Social conditions; Christmas / Southern States / History; Southern States / Social life and customs / 1775-1865; Southern States / Social life and customs / To 1775; Lost Cause mythology; Esclaves / États-Unis (Sud) / Conditions sociales; Noël / États-Unis (Sud) / Histoire; États-Unis (Sud) / Murs et coutumes / Jusqu'à 1775